2017
DOI: 10.3390/s17040828
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Environmental Monitoring System: How to Prevent Systematic Errors in the Design Phase through the Combined Use of Additive Manufacturing and Thermographic Techniques

Abstract: nEMoS (nano Environmental Monitoring System) is a 3D-printed device built following the Do-It-Yourself (DIY) approach. It can be connected to the web and it can be used to assess indoor environmental quality (IEQ). It is built using some low-cost sensors connected to an Arduino microcontroller board. The device is assembled in a small-sized case and both thermohygrometric sensors used to measure the air temperature and relative humidity, and the globe thermometer used to measure the radiant temperature, can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 33 publications
(44 reference statements)
0
22
0
Order By: Relevance
“…Based on the experimental results, the proposed system is robust enough, able to accurately measure the environmental condition in the factory in real-time, and is expected to help managers maintain an optimum working environment for the workers inside the factory. Salamone et al proposed an environmental monitoring system based on low-cost IoT sensors for preventing errors during the design phase in additive manufacturing [ 12 ]. The sensors were used to gather temperature and humidity data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the experimental results, the proposed system is robust enough, able to accurately measure the environmental condition in the factory in real-time, and is expected to help managers maintain an optimum working environment for the workers inside the factory. Salamone et al proposed an environmental monitoring system based on low-cost IoT sensors for preventing errors during the design phase in additive manufacturing [ 12 ]. The sensors were used to gather temperature and humidity data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent technologies such as Internet of Things (IoT)-based sensors can be utilized and integrated with monitoring systems. Studies have been conducted in the manufacturing industry and showed significant benefits from the use of IoT-based sensors for monitoring such as working condition improvements [ 11 ], error design prevention [ 12 ], fault diagnosis [ 13 ], quality prediction [ 14 ], and helping managers with better decision making [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nearable system is described in two papers [6,7]. It's named "nano Environmental Monitoring System" (nEMoS) but, actually, nEMoS could stands for nearable Environmental Monitoring System.…”
Section: Monitoring Systemsmentioning
confidence: 99%
“…Among the several available technologies, those related to control and management of the energy flows within buildings provide good results in terms of diagnosis and optimization of building performance (Zong et al, 2016). This aim is achieved combining building simulation techniques, semantic data models (Terkaj et al, 2014;Gagliardo et al, 2015) and automation processes also through the use of open source hardware for control Salamone et al, 2017) or monitoring purposes . In general, a traditional Energy Management Control System (EMCS) can save between 5% and 15% of energy consumption of buildings (Dong & Lam, 2014).…”
Section: Introductionmentioning
confidence: 99%